2014
DOI: 10.1186/1471-2164-15-100
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of microRNAs in porcine milk exosomes

Abstract: BackgroundBreast milk contains complex nutrients and facilitates the maturation of various biological systems in infants. Exosomes, membranous vesicles of endocytic origin found in different body fluids such as milk, can mediate intercellular communication. We hypothesized that microRNAs (miRNAs), a class of non-coding small RNAs of 18–25 nt which are known to be packaged in exosomes of human, bovine and porcine milk, may play important roles in the development of piglets.ResultsIn this study, exosomes of appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 86 publications
(87 reference statements)
10
162
0
Order By: Relevance
“…Recent studies have shown that immune-related microRNAs are present and enriched in milk [18][19][20][21] suggesting that microRNAs in breast milk may affect development of the immune system, although at present there is no evidence to support these hypotheses.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that immune-related microRNAs are present and enriched in milk [18][19][20][21] suggesting that microRNAs in breast milk may affect development of the immune system, although at present there is no evidence to support these hypotheses.…”
Section: Discussionmentioning
confidence: 98%
“…The real-time PCR thermal profile was as follows: 5 min at 95 °C, 40 cycles of 30 s at 94 °C, 30 s at the corresponding annealing temperature (Tm) and 72 °C for 30 s, followed by 72 °C at 10 min, and 5S ribosomal RNA was used as an internal control for the PCR [17, 34]. The mRNAs primers were designed with Primer 5.0 (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…miR-1343 was identified in several small RNA-sequencing (RNA-seq) studies in humans [27,28], cows [29] and pigs [30,31], although it remains uncharacterized. It is not documented in rodents, suggesting low conservation through evolution.…”
Section: Introductionmentioning
confidence: 99%